If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2x+5x+3=7+3x+2
We move all terms to the left:
2x+5x+3-(7+3x+2)=0
We add all the numbers together, and all the variables
2x+5x-(3x+9)+3=0
We add all the numbers together, and all the variables
7x-(3x+9)+3=0
We get rid of parentheses
7x-3x-9+3=0
We add all the numbers together, and all the variables
4x-6=0
We move all terms containing x to the left, all other terms to the right
4x=6
x=6/4
x=1+1/2
| -(w-36)=-5 | | 1x-7+6=2x-12 | | −6p=36p= | | 85-4x=40 | | 3.2e+2.6=-3 | | 2(x+5)=x+2(x+3) | | 5(2-4)=6h | | m/9+35=-40 | | 3(g-63)=93 | | 7(u+29)=42 | | c/6+47=39 | | 16x²=9 | | n/2+4=-1 | | =14-1/3x | | 9f=2.7 | | 4(x+6)=2-6(x-3) | | 9x=6(x+2)-6=12 | | 13y-9y-13=64.92 | | 7=q/2+6 | | -27x-5=26x | | 16x=15x-11 | | x/9=7/45 | | 3x-x+2=4(2-1) | | 10y-5y-8=60.80 | | 7f=6.3 | | 27=3c-3(6-2c( | | 5/7t+5=2/7t+23 | | 108=4(5a+2) | | 5x-1+3=-12-2x | | 3k-4/2-5k-4/3+1=k-2/3 | | 3k-4/2-5k-4/3+1=k-3/3 | | 3x-x+4=4(2x |